Subchronic Toxicity Study of Sterculia rubiginosa Zoll. Ex Miq. Leaves Extract - Prastiwi, Rini; Hidayati, Ester; Anggraini, Riska; Mauliza, Cut; Anggraini, Ita; Dewanti, Ema (UI Scholars Hub, 2023)
Ki hampelas (Sterculia rubiginosa Zoll. Ex Miq.) is traditionally used as an antiasthma. It also reported has antioxidant and nephroprotective activity. This study was conducted to evaluate the subchronic toxicity of the leaf extract of ki hampelas. The extract was orally administered to male and female Sprague-Dawley rats at doses of 50, 200, and 400 mg/kg bodyweight (BW) per day for 28 days. The rats were divided into four groups, consist of consist of normal group (Na CMC 0.5%), dose 1 (50 mg/kg BW), dose 2 (200 mg/kg BW), and dose 3 (400 mg/ kg BW) of extract. The extract was administered every day for 28 days. Subchronic toxicity in the male and female rats resulted in no death or treatment-related signs at the highest dose. All the animals survived the duration of the study, with no significant changes in biochemical parameters and there was a change in the liver and kidney histopathology results. There was no significant difference between the SGOT, SGPT, urea, and creatinine levels in the dose groups with extracts and the normal group (p > 0.05). However, based on the histological results of the liver and kidneys it was found a significant difference among the groups. This study showed that the leaf extract of ki hampelas is relatively non-toxic according to the normal biochemical parameters results and has no treatment-related signs. There was a change in the liver and kidney histopathology results, but no death was found.